2014
DOI: 10.1002/zaac.201400233
|View full text |Cite
|
Sign up to set email alerts
|

Metal Salts of Dinitro‐, Trinitropyrazole, and Trinitroimidazole

Abstract: The syntheses of alkali and earth alkaline dinitropyrazolate (DNP), trinitropyrazolate (TNP), and trinitroimidazolate (TNI) salts are reported. Additionally, copper trinitroimidazolate was synthesized. Their characterization by NMR spectroscopy, mass spectrometry, elemental analysis, and vibrational spectroscopy is reported as well. Crystal structures of compound Ba(DNP) 2 (9), which crystallizes with one molecule of methanol and ethyl ether as well as of compounds Sr(TNP) 2 ·3H 2 O (12), Ba(TNP) 2 ·3H 2 O (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Zhang et al [109] prepared a series of energetic salts of TNP based on nitrogen-rich cations (61a-m) ( Figure 23, Scheme A), all the salts showed poorer densities and detonation properties than TNP (Table 11), but they owned good thermal stability and excellent insensitivity. Drukenmuller et al [110] reported the synthesis of alkali and earth alkali trinitropyrazolate (62a-d) (Figure 23, Scheme B), compound 62d exhibited predominantly decomposition temperatures (Table 11). They also prepared pyrotechnic formulations using 62c and 62d, which showed good color properties and low sensitivity as well as high T d .…”
Section: Trinitropyrazole and Its Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [109] prepared a series of energetic salts of TNP based on nitrogen-rich cations (61a-m) ( Figure 23, Scheme A), all the salts showed poorer densities and detonation properties than TNP (Table 11), but they owned good thermal stability and excellent insensitivity. Drukenmuller et al [110] reported the synthesis of alkali and earth alkali trinitropyrazolate (62a-d) (Figure 23, Scheme B), compound 62d exhibited predominantly decomposition temperatures (Table 11). They also prepared pyrotechnic formulations using 62c and 62d, which showed good color properties and low sensitivity as well as high T d .…”
Section: Trinitropyrazole and Its Derivativesmentioning
confidence: 99%
“…Property parameters of salts of TNP. The data of compounds 61a-61m are from reference [109], the data of compounds 62a-62d are from reference [110], the data of compounds 63-63g are from reference [111]. Table 11.…”
Section: Trinitropyrazole and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds can have different pharmacological and explosive properties due to the introduction of different groups. Energy groups such as nitro, amino and diazo groups can increase the energy of the compounds [8][9][10][11]. 4-Chloro-3,5-dinitroaniline is the raw material of the precursor 4,4-dichloro-2,2′,3,3′,5,5′,6,6′-octanitroazobenzene of heat resistant explosive.…”
Section: Commentmentioning
confidence: 99%
“…1 At present, we found that energetic salt is a vital part of energetic materials and a large amount of research results have been achieved. [2][3][4][5][6][7] On the account of the lower VP (vapor pressures), higher densities, lower melting points, and higher CED (cohesive energy densities), the salt-based energetic materials have an advantage compared to nonionic energetic materials. According to the empirical equations, the packing density and detonation velocity of explosive has a direct relationship, and the packing density and the detonation pressure of the explosive has a quadratic relationship.…”
Section: Introductionmentioning
confidence: 99%